2018
DOI: 10.3390/su10103547
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Exploitation of Coffee Silverskin in Water Remediation

Abstract: Coffee silverskin (CS), the main solid waste produced from the coffee industry, has efficiently been used as adsorbent material to remove potential toxic metals (PTMs). In order to assess its suitability in water remediation, kinetic adsorption experiments of Cu2+, Zn2+, and Ni2+ ions from wastewater were carried out and the adsorption performance of the waste material was compared with that of another well-known waste from coffee industry, spent coffee grounds (SCG). By using CS as sorbent material, ion remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Recent studies demonstrated that CS could be a valuable source of bioactive compounds such as melanoidins, caffeine and polyphenols, with potential applications of CS extracts as functional ingredients in cosmetic and nutraceutical formulations [ 8 , 10 ]. Other authors have suggested a potential use of this coffee residue as adsorbent material for removal of toxic metals from contaminated water [ 11 ], as a source of cellulose for paper production [ 5 ], and as a prospective ingredient in the food industry. Indeed, Martinez-Saez et al [ 6 ] suggested the use of CS for the production of a novel beverage to be used in body weight control.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that CS could be a valuable source of bioactive compounds such as melanoidins, caffeine and polyphenols, with potential applications of CS extracts as functional ingredients in cosmetic and nutraceutical formulations [ 8 , 10 ]. Other authors have suggested a potential use of this coffee residue as adsorbent material for removal of toxic metals from contaminated water [ 11 ], as a source of cellulose for paper production [ 5 ], and as a prospective ingredient in the food industry. Indeed, Martinez-Saez et al [ 6 ] suggested the use of CS for the production of a novel beverage to be used in body weight control.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological and elemental composition information of the solid anchovy sludge was achieved with a Phenom Pro-X scanning electron microscope (SEM) equipped with an energy-dispersive X-ray (EDX) using the SEM-EDX technique [35].…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images were registered using a Phenom X-Pro microscope (Deben, Suffolk, UK) [ 32 ]. Samples were pasted on a copper foil and analyzed under an accelerating voltage of 5, 10 and 15 kV.…”
Section: Methodsmentioning
confidence: 99%